Effectiveness of Artemisia Vulgaris as Supplementation Against Chemotherapy of Mammae Adenocarcinoma to Reduce Expression of NF-ÎºB and CD 34 (Study in C3H Mice Given Chemotherapy Adriamycin - Cyclophosphamide) - Saputro, Bayu Teguh; Selamat Budijitno (Biomedical Journal of Indonesia, 2021)
Intoduction: Breast cancer is a significant healthcare problem worldwide. Surgery remains the treatment of choice combined with other modalities such as chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). Selective cytotoxicity of AV is intended as a supplementation to Adriamycin-Cyclophosphamide, improving the response rate of chemotherapy in adenocarcinoma mammae. Method: This study used a "Post-test only control group design" on 24 females C3H mice that were randomly selected and divided into four groups: group K (control), P1 (chemotherapy), P2 (extract), and P3 (combination). Adenocarcinoma mammae come from the inoculation of donor mice. Chemotherapy of Adriamycin 60 mg / m 2 and Cyclophosphamide 600 mg / m 2 were given in two cycles. AV 13 mg (0.2 ml) was given once daily orally. NF-ÎºB expression and CD34were evaluated using imunohistochemical staining. Result: The expression of NF-ÎºB and microvascular density of CD 34 were obtained in groups of K, P1, P2, P3 Statistical analysis showed significant decrease in the expression of NF-ÎºB between groups K and P1, P2, P3. Correlation analysis between NF-ÎºB expression with CD 34 was found to have significant correlation (p = 0,039 and r = 0,897). Conclusion:Artemisia vulgaris can reduce angiogenesis by decreasing NF-ÎºB expression and the microvascular density CD34 of adenocarcinoma mammae of C3H mice treated with Adriamycin-Cyclophosphamide chemotherapy and can improve the effectivity.